(untitled) (Medico Legal Update, 2020)
Background: Cervical spinal stenosis is well-defined as debility in the volume of the spinal canal. Consequently, distracting in the descending neural pathways at any level in the cervical spine lead to impaired smooth and effective breathing under normal conditions . Objective: To assess the effect of cervical spinal stenosis (C5and above) on pulmonary function tests , to assess the sensitivity and specificity of pulmonary function tests in patient with cervical spinal stenosis(C5 and above). Methods: This is a case-control study which included 40 patients divided into two groups 30 females and 10 males patients with cervical spinal stenosis (C5 and above) and 60 healthy volunteers with body mass index ? 30 (Kg/m2). Pulmonary function tests has been done for all subjects. Results: The results demonstrate the comparison between all patients and controls show that VC EX% ,FEV1% ,FVC% ,PEF% ,MVV% , were significantly lower in patients in comparison to control groups as well as VC EX %,FEV1%,FVC % were significantly lower in male patients in comparison to controls and in female patients as compared to female controls and MVV% were significantly lower in female patients in comparison to male patients ,while no significant difference has been identified between patients and controls regarding age ,weight , height , BMI,VC IN% and FEV1%. Sensitivity and specificity and cut off value for pulmonary function tests parameters show FEV1% is the highest specificity and sensitivity. Conclusion: The respiratory dysfunction that is established in patients with cervical spinal stenosis usually subclinical not overt defect that compromised respiration ,this pulmonary dysfunction is a type of restrictive lung disease since phrenic nerve is affected. . FEVI% is most essential among other parameters of spirometry in patients with cervical spinal stenosis.